2015
DOI: 10.3390/nano5010270
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Assisted Solubilization of Carbon Nanotubes and Construction of DNA-MWCNT Cross-Linked Hybrid Hydrogels

Abstract: A simple method for preparation of DNA-carbon nanotubes hybrid hydrogel based on a two-step procedure including: (i) solubilization of multi-walled carbon nanotubes (MWCNT) in aqueous solution of DNA, and (ii) chemical cross-linking between solubilized MWCNT via adsorbed DNA and free DNA by ethylene glycol diglycidyl ether is reported. We show that there exists a critical concentration of MWCNT below which a homogeneous dispersion of MWCNT in hybrid hydrogel can be achieved, while at higher concentrations of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…(GT) 20 was chosen as the model ssDNA oligomer because it has been used for the chirality‐specific separation of SWCNTs and because we have found that longer ssDNA strands yield a higher concentration of SWCNT in suspension after probe sonication and centrifugation (typical optical density x dilution factor 20–30, see Figure S1 in the Supporting Information) . The photographs of the suspension in Figure (a) shows the produced SWCNT suspension was stable (for months) and recorded a zeta potential of −42 mV, which is similar to other reports of CNT‐DNA suspensions and similar in magnitude to SWCNT suspensions with anionic surfactant sodium deoxycholate (Figure S2) . SWCNTs dispersed without ssDNA (or surfactant) do not form a stable suspension and do not record a zeta potential value (Figure (a)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(GT) 20 was chosen as the model ssDNA oligomer because it has been used for the chirality‐specific separation of SWCNTs and because we have found that longer ssDNA strands yield a higher concentration of SWCNT in suspension after probe sonication and centrifugation (typical optical density x dilution factor 20–30, see Figure S1 in the Supporting Information) . The photographs of the suspension in Figure (a) shows the produced SWCNT suspension was stable (for months) and recorded a zeta potential of −42 mV, which is similar to other reports of CNT‐DNA suspensions and similar in magnitude to SWCNT suspensions with anionic surfactant sodium deoxycholate (Figure S2) . SWCNTs dispersed without ssDNA (or surfactant) do not form a stable suspension and do not record a zeta potential value (Figure (a)).…”
Section: Resultsmentioning
confidence: 99%
“…[5b] The photographs of the suspension in Figure 1(a) shows the produced SWCNT suspension was stable (for months) and recorded azeta potential of À42 mV,which is similar to other reports of CNT-DNA suspensions and similar in magnitude to SWCNT suspensions with anionic surfactant sodium deoxycholate ( Figure S2). [12] SWCNTsd ispersed without ssDNA (or surfactant) do not form as table suspension and do not record az eta potentialv alue (Figure 2(a)). Furthere vidence for ssDNA adsorption was obtained from Ramans pectroscopy, circulard ichroism and 2D photoluminescence mapping where am inor chirality preference was observed( more detail in Supporting Information, Figure S1 (b)) and Figure S3).…”
Section: Adsorption Of Ssdnamentioning
confidence: 99%
“…These are concentrations 10-fold to 10 3 -fold higher than disclosed in most previous publications, and we do not claim these concentrations are limits. Recent articles report on MWCNT dispersions stabilized by 1-carboxymethy1-3-methylimidazolium bromide 1.2 mg mL −1 in MWCNT (Gunasekaran and Dharmendirakumar, 2014), by 300 base-pair DNA 0.18 mg mL −1 in MWCNT (Zinchenko et al, 2015), and by carbazolemethylstyrenepoly(ethyleneglycol) methyl ether Scheme 2 Triblock copolymer, TB. The subscripts, n, indicating the ILBr end-block lengths can be estimated from molecular weight analyses.…”
Section: Experimental Overviewmentioning
confidence: 99%
“…It seems that aptamers due to their negative charge electrostatic result in repulsion, which has led to the better solubilization and distribution of conjugated nanoparticles. Remarkably, this advantage of DNA was implemented for enhancing the solubility of carbon nanotubes in aqueous solutions, earlier …”
Section: Preparation and Characterization Of Mf‐mwcntsmentioning
confidence: 99%
“…Remarkably, this advantage of DNA was implemented for enhancing the solubility of carbon nanotubes in aqueous solutions, earlier. [36] To visualize the mf-MWCNTs/aptamer complexes, following the interaction of carbon nanotubes to aptamers, transmission electron microscope images in the presence and absence of aptamer were obtained. As it is demonstrated in Figure S11, in the presence of aptamers, some halos are seen around carbon nanotubesparticularly in the node-like structures related to Fe 3 O 4 nanoparticles which seem to pertain to the condensation of DNA oligonucleotides at this spots (they are absent in the images obtained from mf-MWCNTs alone).…”
Section: Binding Of Mf-mwcnts To Aptamer and Plasmidmentioning
confidence: 99%